Respuestas
Respuesta dada por:
3
32x - 25y = 13
16x + 15y = 1 (×2)
--------------------
32x - 25y = 13 (restamos)
32x + 30y = 2
---------------------
-55y = 11
y = -![\frac{11}{55} \frac{11}{55}](https://tex.z-dn.net/?f=+%5Cfrac%7B11%7D%7B55%7D+)
y = -![\frac{1}{5} \frac{1}{5}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B5%7D+)
Reemplazamos "y" en cualquier ecuación:
32x - 25y = 13
32x - 25(-
) = 13
32x +
= 13
32x + 5 = 13
32x = 8
x =![\frac{8}{32} \frac{8}{32}](https://tex.z-dn.net/?f=+%5Cfrac%7B8%7D%7B32%7D+)
x =![\frac{1}{4} \frac{1}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B4%7D+)
Comprobamos "x" and "y" en la última ecuación:
16x + 15y = 1
16(
) + 15(-
) = 1
-
= 1
4 - 3 = 1
1 = 1
Rpta:
x =![\frac{1}{4} \frac{1}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B4%7D+)
y = -![\frac{1}{5} \frac{1}{5}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B5%7D+)
Listo...
16x + 15y = 1 (×2)
--------------------
32x - 25y = 13 (restamos)
32x + 30y = 2
---------------------
-55y = 11
y = -
y = -
Reemplazamos "y" en cualquier ecuación:
32x - 25y = 13
32x - 25(-
32x +
32x + 5 = 13
32x = 8
x =
x =
Comprobamos "x" and "y" en la última ecuación:
16x + 15y = 1
16(
4 - 3 = 1
1 = 1
Rpta:
x =
y = -
Listo...
GT2018:
seguro que es asi??
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años